Penentuan Rute Distribusi Optimal di PB Surya Agung dengan Menggunakan Metode Saving Matrix, Nearest Insertion dan Software LINGO - Hasanah, Kori; Winarno, Winarno (Universitas Batanghari Jambi, 2025)
This research aims to determine the optimal distribution route for rice products in PB Surya Agung by utilizing the Saving Matrix and Nearest Insertion methods as well as using LINGO software. The Saving Matrix method is used to identify the most efficient route in the distribution process, while the Nearest Insertion method is used to insert new nodes into existing routes. The research results show that combining the two is able to increase the distribution efficiency of rice products in the company. Through this approach, PB Surya Agung can optimize the distribution route for their rice products to achieve maximum efficiency and effectiveness.